Maternal bereavement and the risk of preterm delivery: the importance of gestational age and of the precursor of preterm birth. Issue 6 (8th December 2015) - László, K. D.; Li, J.; Olsen, J.; Vestergaard, M.; Obel, C.; Cnattingius, S.
Abstract : Background: Maternal stress during pregnancy may increase the risk of preterm delivery (PD), but the associations between stress and subtypes of PD are not clear. We investigated maternal loss of a close relative and risks of very and moderately PD (<32 and 32–36 weeks, respectively) and spontaneous and medically indicated PD. Method: We studied 4 940 764 live singleton births in Denmark (1978–2008) and Sweden (1973–2006). We retrieved information on death of women's family members (children, partner, siblings, parents), birth outcomes and maternal characteristics from nationwide registries. Results: Overall, the death of a close family member the year before pregnancy or in the first 36 weeks of pregnancy was associated with a 7% increased risk of PD [95% confidence interval (CI) 1.04–1.10]. The highest hazard ratios (HR) for PD were found for death of an older child [HR (95% CI) 1.20 (1.10–1.31)] and for death of a partner [HR (95% CI) 1.31 (1.03–1.66)]. These losses were associated with higher risks of very preterm [HR (95% CI) 1.61 (1.29–2.01) and 2.07 (1.15–3.74), respectively] than of moderately preterm [HR (95% CI) 1.14 (1.03–1.26) and 1.22 (0.94–1.58), respectively] delivery. There were no substantial differences in the association between death of a child or partner and the risk of spontaneous v. medically indicated PD. Conclusions: Death of a close family member the year before or during pregnancy was associated with an increased risk of PD, especially very PD. Possible mechanisms include both spontaneous and medically indicated preterm birth.